Hydrogen Permeation Through Glass - Welter, Thorben; Müller, Ralf; Deubener, Joachim; Marzok, Ulrich; Reinsch, Stefan (Frontiers in Materials, 2020)
Physical storage of gaseous hydrogen under high-pressure in glassy micro-containers such as spheres and capillaries is a promising concept for enhancing safety and the volumetric capacity of mobile hydrogen storage systems. As very low permeation through the container wall is required for storage of compressed hydrogen, development of glasses of minimal hydrogen permeability is needed. For this purpose, one has to understand better the dependence of hydrogen permeability on glass structure. The paper points out that minimizing the accessible free volume is a sound strategy to minimize hydrogen permeability. Based on previously measured and comprehensive literature data, it is shown that permeation is independently controlled by ionic porosity and network modifier content. Thus, ionic porosity in modified and fully polymerized networks can be decreased equally to the lowest hydrogen permeability among the glasses under study. Applying this concept, a drop of up to 30,000 with respect to the permeation of hydrogen molecules through silica glass is attainable.